Multiple rim-enhancing brain lesions and pulmonary cavitary nodules as the presentation of Nocardia cyriacigeorgica in a patient with non–small cell lung cancer. Issue 4 (9th June 2022) - Bejcek, Alexis; Owens, Justin; Marella, Aditi; George, Aneesh
Abstract: Nocardiosis is caused by various strains of the genus Nocardia, a gram-positive, acid-fast bacillus found in organic matter. Disseminated nocardiosis with central nervous system involvement is a rare infection that is most commonly seen in immunocompromised patients. We present a case of a 67-year-old veteran with stage IV adenocarcinoma of the lung undergoing chemotherapy who presented with new cavitary pulmonary lesions. Three weeks into his hospitalization, a sputum culture with acid-fast staining returned positive for Nocardia cyriacigeorgica . A subsequent computed tomography scan of the head demonstrated numerous rim-enhancing lesions presumed to be due to disseminated nocardiosis with central nervous system involvement. Disseminated nocardiosis has a high mortality rate, making prompt detection and treatment paramount for these patients. Our case highlights the importance of considering central nervous system involvement in the evaluation of a patient with nocardiosis.